Evaluation of the Utility of the Random Amplified Polymorphic DNA Method and of the Semi-Specific PCR to Assess the Genetic Diversification of the Gerbera jamesonii Bolus Line - Zbigniew Rusinowski; Olga Domeradzka (The Scientific World Journal)
An attempt was made to evaluate the utility of a method which employs semi-specific PCR using partially specific primers for the coding sequence (ET) at the exon-intron contact and of the RAPD method to identify eight Polish cultivars of gerbera. It was demonstrated that the PCR method which employs semi-specific primers is as simple and economical as the RAPD method, simultaneously the images of the multiplied by means of the semi-specific PCR method DNA fragments are more complex and polymorphic than those obtained through the RAPD method. The studies of the genetic diversification of Gerbera cultivars employing the aforementioned methods made it possible to conduct a concentration analysis and evaluation of the genetic distance between the lines, manifesting at the same time the superiority of the semi-random PCR method. Moreover, it transpired that the use of mixtures of RAPD primers not always leads to an increase of the number of generated polymorphic bands.